The new regionalism and policy interdependence - Leonardo Baccini; Andreas Dür (University of Salzburg, Department of Social Sciences and Economics, 2010)
Since 1990 the number of preferential trade agreements has increased rapidly. Our argument explains this phenomenon, known as the new regionalism, as a result of competition for market access. Exporters that face trade diversion because of their exclusion from a preferential trade agreement concluded by foreign countries push their governments into signing an agreement with the country in which their exports are threatened. We test our argument in a quantitative analysis of the proliferation of preferential trade agreements among 167 countries between 1990 and 2007. The finding that competition for market access is a major driving force of the new regionalism is a contribution to the literature on regionalism and to broader debates about global economic regulation.
Keywords: 330